Implementasi Sapta Pesona Pada Glamorous Camping Kema Merbabu - Imanina, Almas Nabili; Jannah, Desika Nur; Arvianto, Bram (Jurnal Ilmiah Pariwisata, 2024)
The existence of creative development and innovation in the management of tourist attractions is currently bringing glamping as a current trend. Glamping (glamorous camping) refers to a modern camping concept that combines the essence of nature with adequate facilities. Boyolali Regency is an area in Central Java which is very famous for the production of quality milk and cheese from various dairy farms, where this area is also called New Zealand Van Java. The glamping accommodation trend can be said to be very suitable to be implemented in Boyolali considering that the weather in this area can be said to be cool. Boyolali Regency has 3 accommodations with a glamor camping concept which are quite competitive and well known to tourists, one of which is Kema Merbabu. The application of the concept of conscious tourism and Sapta Pesona is important in the basis of its development because it can encourage public awareness to become a host. which is good for tourists. Through descriptive qualitative research and observation and interview methods, the 7 elements contained in Sapta Pesona in Kema Merbabu still contain many potential tourism activities and products that can be developed so that Kema Merbabu can attract more tourists and extend the length of their stay. Keywords: implementation, sapta pesona, glamping